Electrical load forecasting : modeling and model construction - Soliman, S. A. (Butterworth-Heinemann, 2010)
Succinct and understandable, this book is a step-by-step guide to the mathematics and construction of Electrical Load Forecasting models. Written by one of the world's foremost experts on the subject, Short and Long Term Electrical Load Forecasting provides a brief discussion of algorithms, there advantages and disadvantages and when they are best utilized. Supported by an online computer program, this book online arrangement allows readers construct, validate, and run short and long term models. The book begins with a brief discussion algorithm, there advantages and disadvantages and when they are best utilized. This is followed by a clear and rigorous exposition of the statistical techniques and algorithms such as regression, neural networks, fuzzy logic, and expert systems. In this book, readers find reliable and easy-to-use techniques designed to improve their forecasting techniques and construct more accurate models. The book begins with a good description of the basic theory and models needed to truly understand how the models are prepared so that they are not just blindly plugging and chugging numbers. Step-by-step guide to model construction Construct, verify, and run short and long term models Accurately evaluate load shape and pricing Creat regional specific electrical load models.